Immobilization of oil and grease in sodium alginate gel as a potential wastewater treatment method - Jami, Mohammed Saedi; Mohd. Salleh, Hamzah; Abd Kadir, Zarith Elda; Tanaka, Takanori; Iwata, Masashi (2013)
In this study, oil-entrapped sodium alginate beads were developed and their effectiveness in treating oil and grease (O&G) from wastewater was investigated. The effect of polymer concentration and pH on the O&G entrapment efficiency (OEE) as well as the biodegradability of gel beads were investigated. O&G were immobilized in sodium alginate gels by adding a mixture of alginate and car wax aqueous solution into a calcium chloride aqueous solution, resulting in sodium alginate gels. The gel suspensions were dehydrated gravitationally, followed by mechanical expression of gel particles. During the expression, the O&G remain in the gels. The expressed cake is then discarded. Results showed that OEE increased by increasing sodium alginate concentration from 17 g/l to 50 g/l. Further inspection of the results found that increasing pH of sodium alginate from 1.8 to 7 also increased the OEE in the beads. It was observed that sodium alginate beads experienced complete biodegradation in phosphate buffer pH 8.0.